Implementasi Penggunaan Gim Edukatif Digital untuk Meningkatkan Pemahaman Konsep Pecahan dalam Mata Pelajaran Matematika Siswa Kelas V Sekolah Dasar - Najla Imtinan; Ibnu Muthi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to examine the implementation of digital educational games to enhance the understanding of fraction concepts among fifth-grade elementary school students. The background of this research lies in the low mastery of fraction material and the lack of student engagement due to conventional teaching approaches. The research used a quasi-experimental method with a pretest-posttest control group design. The subjects were divided into an experimental group, which received digital educational game-based learning, and a control group, which was taught using traditional lectures and practice questions. The results showed a significant improvement in the understanding of fractions in the experimental group compared to the control group. The findings indicate that digital educational games can enhance motivation, engagement, and the effectiveness of mathematics learning. This research recommends the integration of interactive digital media as an innovative strategy for teaching mathematics in elementary schools.